2022
DOI: 10.1002/eap.2764
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genetic sources facilitate the northward range expansion of an intertidal oyster along China's coast

Abstract: Coastal artificial structures on the former mudflats provide available habitats for the rocky intertidal species which can establish new populations in these emerging habitats over their former distribution range limits. As a former southern species, the oyster Crassostrea sikamea has become a pioneer and rapidly invaded the artificial shorelines in northern China. We used a seascape genomics approach to investigate the population structure and genetic sources of C. sikamea on the coastal artificial structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 94 publications
(127 reference statements)
5
3
0
Order By: Relevance
“…Likewise, population structure between the expanded range and core populations was found for the intertidal gastropod, Nerita yoldii , along the Chinese coast (Wang et al., 2022) and the octopus Octopus tetricus , along the western Australian coast (Ramos et al., 2018). In contrast, our results mirror those seen in a range expansion of the sea urchin, Centrostephanus rodgersii (Banks et al., 2010), the oyster, Crassostrea sikamea (Hu & Dong, 2022), and the barnacle, Tetraclita rubescens (Dawson et al., 2010), showing no evidence of population structure or a decrease in genetic diversity at the expanded‐range edge.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, population structure between the expanded range and core populations was found for the intertidal gastropod, Nerita yoldii , along the Chinese coast (Wang et al., 2022) and the octopus Octopus tetricus , along the western Australian coast (Ramos et al., 2018). In contrast, our results mirror those seen in a range expansion of the sea urchin, Centrostephanus rodgersii (Banks et al., 2010), the oyster, Crassostrea sikamea (Hu & Dong, 2022), and the barnacle, Tetraclita rubescens (Dawson et al., 2010), showing no evidence of population structure or a decrease in genetic diversity at the expanded‐range edge.…”
Section: Discussionsupporting
confidence: 82%
“…anatifera in the northwest Pacific. As previous studies reported (Han & Dong, 2020 ; Hu & Dong, 2022b ), the genetic variations among populations of the mussel Mytilus galloprovincialis and the oyster Crassostrea sikamea were significantly correlated with the environmental temperatures. In the present study, the results of RDA analysis revealed that local temperature, especially the low temperature in January (e.g., T1) was a significant factor influencing the distribution patterns of putatively adaptive genetic variation among populations.…”
Section: Discussionsupporting
confidence: 69%
“…These results implied that temperature heterogeneity might be a physical barrier that prevents the gene flow between lineages with different thermal tolerances and plays a vital role in maintaining the genetic differentiation patterns of L. anatifera from the fixed buoys in the NWP.The redundancy analysis based on the genotype-environment association method further confirmed the roles of temperature heterogeneity in maintaining the genetic differentiation of L. anatifera in the northwest Pacific. As previous studies reported(Han & Dong, 2020;Hu & Dong, 2022b), the genetic variations among populations of the mussel Mytilus galloprovincialis and the oyster Crassostrea sikamea were significantly correlated with the environmental temperatures.…”
supporting
confidence: 64%
“…From a biogeographical perspective, understanding the role of climate change and human activities in driving the distribution of alien species is crucial for predicting adaptive capabilities and future invasion potentials. A study by Hu and Dong (2023) on the marine species Crassostrea sikamea demonstrated that the rapid northward expansion of the southern population, in response to climate change and coastal development, was facilitated by multiple sources of divergent thermal adaptability. These findings provide valuable insights into the genetic origins and dispersal mechanisms of intertidal oysters during their northward shift along China's coast, highlighting the importance of rapid adaptation to local environments in driving distribution shifts and preserving population viability at the distribution edge.…”
Section: Mechanisms Of Invasion Successmentioning
confidence: 99%